2020
DOI: 10.3390/su12072645
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Capital: ISVA, the Alternative Way of Calculating Creating Value in Agricultural Entities—Case of Poland

Abstract: In the knowledge-based economy, knowledge is regarded as a strategic resource that helps entities to become market leaders. This strategy has been successfully used for years by companies operating in various sectors of the economy. The exception, however, is agriculture, which has been seen for years as a sector with low knowledge intensity and is one that is skeptical about the possibility of using knowledge. This is important especially in that the use of it is, for many managers, still unconscious, and, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Lastly, Kozera-Kowalska (2020) assessed if IC aids agriculture’s shift toward sustainability, proposing a new metric, Intellectual Source of Value Added (ISVA). Data from 120 Polish farms (2005–2018) suggested that agricultural entities, though perceived as low-knowledge, efficiently utilize IC, making ISVA more suitable than VAIC™.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, Kozera-Kowalska (2020) assessed if IC aids agriculture’s shift toward sustainability, proposing a new metric, Intellectual Source of Value Added (ISVA). Data from 120 Polish farms (2005–2018) suggested that agricultural entities, though perceived as low-knowledge, efficiently utilize IC, making ISVA more suitable than VAIC™.…”
Section: Resultsmentioning
confidence: 99%
“…We use the value added intellectual coefficient (VAIC) method. According to Sumedrea (2013), Kozera-Kowalska (2020), Palazzi et al (2020), and Kramaric et al (2021), the VAIC model (Pulic, 2004) reflects the value creation efficiency of the resources with the advantage of using financial data and then making comparison between different firms' performance easy; it is shown by a series of steps including the value added (VA), human capital efficiency (HCE), structural capital efficiency (SCE) and capital employed efficiency (CEE). First, the value added (VA) is obtained as the sum of operating profit (OP), employee costs (EC), depreciation expenses (DP), and amortization expenses (AM).…”
Section: Methodsmentioning
confidence: 99%
“…The strategic alliance lies in the creativity of cooperation. The strategic alliance lies in the spirit of cooperation and development that is based on a relationship of mutual trust and allows to reach specific goals by mutual agreement (Areiqat and Jaradat, 2012) Alliances differ by type of relationship, a degree rationality, understanding, the size of risks, information, interests and the circumstances of the surrounding environment (Magdalena, 2020).…”
Section: Relational Capitalmentioning
confidence: 99%